Free Cash Flow, Investment Aggressiveness, and Growth Policy on Dividend Safety - Gunawan, William Ben (Jurnal Akuntansi, 2026)
This study analyzes the relationship between free cash flow and dividend safety, moderated by investment aggressiveness and growth policy, in companies listed on the IDX High Dividend 20 during the 2021–2024 period. Using a quantitative approach with PLS-SEM, the results show that free cash flow and growth policy have a positive and significant effect on dividend safety. This indicates that strong free cash flow availability and an aggressive growth policy are crucial factors for companies to sustain dividends safely. In contrast, investment aggressiveness does not have a significant effect on dividend safety. Furthermore, both moderating variables are not proven to influence the relationship between free cash flow and dividend safety. These findings suggest that for companies consistently distributing dividends, the ability to generate free cash flow and adopt growth strategies are the main determinants of dividend safety, regardless of the level of investment aggressiveness. The managerial implication of this study is the importance of focusing on free cash flow management to maintain dividend stability and investor confidence.